Comparative investigation on Yb:YAG and Yb:LuAG transparent laser ceramics. Issue 10 (December 2015) - Ma, Chaoyang; Tang, Fei; Wen, Zicheng; Du, Miaomiao; Zhang, Jiantao; Long, Jiaqi; Yuan, Xuanyi; Guo, Wang; Cao, Yongge; Wang, Liujiu
Abstract: Both Yb:YAG and Yb:LuAG transparent ceramics were fabricated by vacuum sintering technology. Phase identification, surface morphologies and laser characteristics were comparatively investigated. For the optical transmittance spectrum of pre-annealing samples, absorption peaks of Yb:LuAG show a large blue shift in the visible region compared with that of Yb:YAG ceramics. The emission intensity gradually decreases with the rise of temperature. The fitting result of fluorescence decay curve shows the lifetimes of Yb 3+ ions at 1030 nm to be 1.23 ms for Yb:YAG and 1.50 ms for Yb:LuAG ceramics. Pumped by a 970 nm diode laser, the slop efficiency was 33% for 5.0at.% Yb:LuAG ceramic with the maximum laser output of 881 mW at the absorbed pump power of 3.3 W. By comparison, the slope efficiency of 24% was achieved for 5.0 at% Yb:YAG transparent ceramic.